Future business trends and higher secondary school business studies curriculum - Chiew, M.Y.; Siraj, Saedah; Mahabubul Alam, G. (2010)
In the business world, business is about creating value for stakeholders. Stakeholders want business professionals who are responsible towards the business community and society. The curriculum of Business Studies (BS) is responsible to mould high school leavers into entrepreneurs or continue to institutions of higher learning. BS of Malaysia is a decade old but not moderated or revised. There is a need to know whether the present curriculum is catering to future business needs. This is a preliminary and ongoing study. This study explores future business trends, business competencies needed of school leavers, and the content of BS curriculum of the future. A qualitative approach is used, whereby stakeholders were interviewed and review of literature was carried out. Generic skills and apprenticeship are advocated in the future BS curriculum.